Integration of Fruit and Vegetables in the Food of Oreochromis Niloticus in the Vakinankaratra Region - Rindra, Rabarison; Nicole, Ravelomanantsoa Ramanambe; Tahina, Rabeharitsara Andry; Pierre, Rakotomamonjy; Ngbolua, Koto-te- Nyiwa; Baholy, Robijaona Rahelivololoniaina (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
In order to promote the nutrition of tilapia in farming, a food has been created from traditional raw materials and containing a quantity of banana flour and carrot flour from local production 3%. We tested the food which contains 33% crude proteins and 8% lipids on carp fry having an initial weight of 99.56 ±1.12 gr during 50 days in Vakinankaratra region, Madagascar . After 50 days of experiment, the final weights of the fish fluctuated between 187.63g and 188.15g depending on the treatments used. The food containing banana flour, carrot and the control food showed almost similar growth and food transformation rates, with specific growth rates (SGR) of 3.12%/d and 3.14%/ j as well as a conversion rate of 1.5 and 1.5. Thanks to this test, we were able to observe the impact of banana and carrot on the development of tilapia. We will continue to study the use of local agri-food by-products and waste in feeding this fish.